JS04.4.A Beyond β-catenin: Genetic alterations ofTP53 andOTX2 and older age indicate increased risk of relapse in WNT medulloblastomas. (5th September 2022) - Goschzik, T; Mynarek, M; Doerner, E; Spier, I; Warmuth-Metz, M; Bison, B; Obrecht, D; Struve, N; Kortmann, R; Hau, P; Aretz, S; Rutkowski, S; et al.
Abstract: Background: This genetic analysis of WNT-activated medulloblastomas (WNT-MBs) aimed to re-evaluate the prognostic impact of age, TP53 mutations and to identify specific chromosomal aberrations as possible prognostic markers. Material and Methods: In a cohort of 191 patients with WNT-MBs, mutations in CTNNB1, APC and TP53 were analyzed by Sanger and/or NGS panel sequencing. Chromosomal copy number aberrations were assessed by high-resolution, genome-wide molecular inversion probe technology (MIP), SNP6 array, and/or 850k methylation bead-array hybridization. Association with prognosis was evaluated in 133 patients with follow-up data from the HIT2000 medulloblastoma trial, HIT registries, and the NOA-07 trial. Results: CTNNB1 mutations were present in 92.2% of the samples. APC mutations were found in 6.8% (13 samples). One CTNNB1 wildtype tumor gained WNT-activation due to a homozygous deletion of FBXW7 . Monosomy 6 was present in 78.6%, and more frequent in children compared to adolescents/adults (≥16 years). Adolescents/adults showed worse overall survival (OS; p =0.009) compared to children, but not worse progression-free survival (PFS; p =0.106). With an age cut-off at 18 years, no survival difference was found. Also adolescents alone (16-20 years) had worse OS ( p =0.003) compared to children, whereas in patients ≥21 (n=12 adults with PFS/OS data) no tumor progression/relapse occurred. Only one adult died due to therapy-related complications. WNT-MB patients with tumors harboring TP53 mutations (24/133, 18.1%) showed significant worse PFS ( p =0.001), which was also found in children and adolescents individually ( p =0.004, resp. p =0.017). Gains of the OTX2 locus on chromosome 14q found in 40.2% (35/87) of samples were independent of TP53 mutations and also associated with poor PFS and OS (p =0.034, resp. p =0.016). Individual analyses of OTX2 gains within age groups showed only worse OS in children ( p =0.012). Multivariate Cox regression analysis for PFS identified both genetic alterations, but not age, as independent prognostic markers. For OS, multivariate analysis found OTX2 gains and older age as independent prognostic markers. Conclusion: Our data suggest that adolescent patients with WNT-MB and those patients carrying TP53 mutations or OTX2 gains - independent of age - are at higher risk of relapse. Eligibility of these patients for therapy de-escalation trials needs to be debated.